Strategi Pemeliharaan Dan Model Hubungan Antara Nilai Kekasaran Jalan Dan Nilai Kondisi Perkerasan Kaku Dengan Metode IKP Dan IRI Studi Kasus Jalan Lingkar Selatan Kota Cilegon - Saputra, Eka; Parianta, Arbi; Oka Mahendra, M (Prosiding TAU SNARS-TEK Seminar Nasional Rekayasa dan Teknologi, 2025)
Damage to roads indicates a condition where the structural and functional aspects of the road are no longer able to provide optimal service to the traffic passing through it. If road damage occurs, it can result not only in the obstruction of economic and social activities but also in the occurrence of accidents. To determine the level of damage and the type of repairs needed for a road segment under review, a method is required. In this study, the IKP method (Pavement Condition Index) and IRI method (International Roughness Index) are used. The objectives of this research are to determine the road damage level using the IKP method on the South Cilegon Ring Road, to determine the road roughness level using the IRI method on the South Cilegon Ring Road, to compare the values of road damage level using the IKP and IRI methods on the South Cilegon Ring Road, and to address road damage based on the road condition assessment results. The results of this study show that there are five types of damage on the South Cilegon Ring Road in both the right and left lanes: Line cracks, Punchout, Plate Separator, Corner cracks, and Large patches. The smoothness level (IRI) on the South Cilegon Ring Road in the left lane is in good condition with percentage values of 60% for good, 15% for fair, and 25% for severe damage. Meanwhile, in the right lane, the road condition is good with percentage values of 75% for good, 20% for fair, and 5% for light damage. The proposed solution for road condition management on the South Cilegon Ring Road as a whole, following Regulation of the Minister of Public Works No. 13/PRT/M/2011, is a routine maintenance program. The relationship between the road roughness value (IRI) and the road pavement damage value (IKP) is analyzed through regression analysis, resulting in the equation IKP = 0.0012(IRI)^2 – 0.1648(IRI) + 8.8719.